Имена и курганы архаического периода - Кузнецова, Т.М. (Археологія і давня історія України, 2019)
В статье рассматриваются вопросы скифской археологии, связанные с атрибуцией архаических захоронений и определением имен исторических персонажей, для которых они могли быть сооружены. The article deals with the issues of Scythian archaeology related to the attribution of archaic burials and the definition of the names of historical characters for which they could be built. According to the author of excavation, the Scythian king Madyes, son of Protothyes, was buried in the barrow 1 of the Krasnoznamensky burial ground.